Geochemical signatures in plastic debris from the Curonian Lagoon, Lithuania - Sajjad Abbasi; Neda Hashemi; Patryk Oleszczuk; Viktorija Sabaliauskaitė; Nerijus Dzingelevičius; Arūnas Balčiūnas; Rita Vaičekauskaitė; Reda Dzingelevičienė (PLoS ONE, 2026)
This study examined elemental accumulation on weathered plastic waste as a contributor to environmental pollution. Twenty-five plastic samples collected near the Curonian Lagoon in Lithuania were analyzed for 32 elements using inductively coupled plasma-mass spectrometer (ICP-MS). Five common polymers (polyethylene, polypropylene, Polyethersulfone, polyester, and polyethylene terephthalate) were identified, with polyethylene exhibiting the highest elemental uptake, followed by polypropylene and polystyrene. Correlation analysis suggested relationships between elemental uptake and geochemical behavior, with alkali and alkaline earth elements (REEs) potentially enhancing the uptake of intermediate ions. However, elements such as sulfur, lead, cadmium, and antimony showed limited correlation with other elements. Despite their low mobility, REEs were used to infer sources of pollution, and the aluminum to lanthanum ratio was proposed as a potential indicator of possible anthropogenic pollution from industrial, petroleum, and vehicle emissions.